The effects of creatine supplementation on cardiovascular, metabolic, and thermoregulatory responses during exercise in the heat in endurance-trained humans - Kilduff, L. P.; Georgiades, E.; James, N.; Minnion, R. H.; Mitchell, M.; Kingsmore, D.; Hadjicharalambous, M.; Pitsiladis, Y. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
The effects of creatine (Cr) supplementation on cardiovascular, metabolic, and thermoregulatory responses, and on the capacity of trained humans to perform prolonged exercise in the heat was examined. Endurance-trained males (n = 21) performed 2 constant-load exercise tests to exhaustion at 63 ± 5 % VO in the heat (ambient temperature: 30.3 ± 0.5 °C) before and after 7 d of Cr (20 g × d-1 Cr + 140 g × d-1 glucose polymer) or placebo. Cr increased intracellular water and reduced thermoregulatory and cardiovascular responses (e.g., heart rate, rectal temperature, sweat rate) but did not significantly increase time to exhaustion (47.0 ± 4.7 min vs. 49.7 ± 7.5 min, P = 0.095). Time to exhaustion was increased significantly in subjects whose estimated intramuscular Cr levels were substantially increased ("responders": 47.3 ± 4.9 min vs. 51.7 ± 7.4 min, P = 0.031). Cr-induced hyperhydration can result in a more efficient thermoregulatory response during prolonged exercise in the heat.